2010
DOI: 10.4161/auto.6.6.12510
|View full text |Cite
|
Sign up to set email alerts
|

A reporter cell system to monitor autophagy based on p62/SQSTM1

Abstract: M acroautophagy (hereafter referred to as autophagy) is a catabolic pathway to isolate and transport cytosolic components to the lysosome for degradation. Recently, autophagy receptors, like p62/SQSTM1 and NBR1, which physically link autophagic cargo to ATG8/MAP1-LC3/GABARAP family members located on the forming autophagic membranes, have been identified. To identify conditions or compounds that affect autophagy, cell systems that efficiently report on autophagic flux are required. Here we describe reporter ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 31 publications
6
105
1
Order By: Relevance
“…In the process, SQSTM1 is degraded through autophagy; accordingly, a decrease in SQSTM1 is considered indicative of enhanced autophagic flux. 38,39 We observed that treatment with AMA led to an increase in SQSTM1 levels in HL-1 cells and that coincubation with rapamycin decreased its accumulation (Fig. 4B).…”
Section: Ama Increases Mitochondrial Omentioning
confidence: 82%
“…In the process, SQSTM1 is degraded through autophagy; accordingly, a decrease in SQSTM1 is considered indicative of enhanced autophagic flux. 38,39 We observed that treatment with AMA led to an increase in SQSTM1 levels in HL-1 cells and that coincubation with rapamycin decreased its accumulation (Fig. 4B).…”
Section: Ama Increases Mitochondrial Omentioning
confidence: 82%
“…S1A). To confirm this, we applied a novel reporter cell system based on induced expression of p62-GFP, where the degradation of GFP can be followed after promoter shutoff by flow cytometry (16). In accordance with the autophagic flux assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…p62-GFP cells were cultured in DMEM plus GlutaMAX supplemented with 15 g/ml hygromycin, 200 g/ml blasticidin, and 10% FCS (16). Cells were grown at 37°C and 10% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a reporter system to monitor autophagy in mammalian cells based on p62 has been proposed. 69 According to the authors, the GFP-p62 performed the best among the three tested reporter fusions (GFP-LC3, GFP-NBR1 and GFP-p62) and was the most useful in screening for compounds or conditions that affected the rate of autophagy.…”
Section: Discussionmentioning
confidence: 99%